Acute stroke with major intracranial vessel occlusion: Characteristics of cardioembolism and atherosclerosis-related in situ stenosis/occlusion. (October 2016) - Horie, Nobutaka; Tateishi, Yohei; Morikawa, Minoru; Morofuji, Yoichi; Hayashi, Kentaro; Izumo, Tsuyoshi; Tsujino, Akira; Nagata, Izumi; Matsuo, Takayuki
Highlights: Acute stroke accompanying major vessel occlusion is different depending on stroke subtype. Susceptibility vessel sign is significantly related to cardioembolic stroke. Intra-arterial signal on ASL and FLAIR are useful to distinguish acute occlusion from chronic occlusion. Abstract: Acute ischemic stroke with major intracranial vessel occlusion is commonly due to cardioembolic or atherosclerosis-related in situ stenosis/occlusion, and immediate identification of these subtypes is important to establish the optimal treatment strategy. The aim of this study was to clarify the differences in clinical presentation, radiological findings, neurological temporal courses, and outcomes between these etiologies, which have not been fully evaluated. Consecutive emergency patients with acute ischemic stroke were retrospectively reviewed. Among them, patients with stroke with major intracranial vessel occlusion were analyzed with a focus on clinical and radiological findings, and a comparison was performed for those with cardioembolic or atherosclerosis-related in situ stenosis/occlusion. Of 1053 patients, 80 had stroke with acute major intracranial vessel occlusion (45 with cardioembolic and 35 with atherosclerosis-related in situ stenosis/occlusion). Interestingly, the susceptibility vessel sign (SVS) on T2-weighted MR angiography was more frequently detected in cardioembolic stroke (80.0%) than in atherosclerosis ( in situ stenosis: 5.9%, chronic occlusion: 14.3%). Moreover, the proximal intra-arterial signal (IAS) on arterial spin labeling MRI and the distal IAS on fluid attenuated inversion recovery MRI was less frequently detected in chronic occlusion (27.3% and 50.0%, respectively) than in acute occlusion due to cardioembolic or in situ stenosis. Multivariate regression analysis showed that the SVS was significantly related to cardioembolism (adjusted odds ratio (OR): 21.68, P  = 0.004). Clinical characteristics of acute stroke with major intracranial vessel occlusion differ depending on the etiology. The SVS and proximal/distal IAS on MRI are useful to distinguish between cardioembolic and atherosclerotic-related in situ stenosis/occlusion.